Circadian Effects on Performance and Effort in Collegiate Swimmers. (3rd August 2018) - Anderson, Austin; Murray, Gillian; Herlihy, Meaghan; Weiss, Chloe; King, Jacob; Hutchinson, Ellen; Albert, Neil; Ingram, Krista K.
Although individual athletic performance generally tends to peak in the evening, individuals who exhibit a strong diurnal preference perform better closer to their circadian peak. Time-of-day performance effects are influenced by circadian phenotype (diurnal preference and chronotype—sleep-wake patterns), homeostatic energy reserves and, potentially, genotype, yet little is known about how these factors influence physiological effort. Here, we investigate the effects of time of day, diurnal preference, chronotype, and PER3 (a circadian clock gene) genotype on both effort and performance in a population of Division I collegiate swimmers (n = 27). Participants competed in 200m time trials at 7:00 and 19:00 and were sampled pre- and post-trial for salivary α-amylase levels (as a measure of physiological effort), allowing for per-individual measures of performance and physiological effort. Hair samples were collected for genotype analysis (a variable-number tandem-repeat (VNTR) and a single nucleotide polymorphism (SNP) in PER3 ). Our results indicate significant and parallel time-of-day by circadian phenotype effects on swim performance and effort; evening-type swimmers swam on average 6% slower with 50% greater α-amylase levels in the morning than they did in the evening, and morning types required 5–7 times more effort in the evening trial to achieve the same performance result as the morning trial. In addition, our results suggest that these performance effects may be influenced by gene (circadian clock gene PER3 variants) by environment (time of day) interactions. Participants homozygous for the PER3 4, 4 length variant (rs57875989) or who possess a single G-allele at PER3 SNP rs228697 swam 3–6% slower in the morning. Overall, these results suggest that intra-individual variation in athletic performance and effort with time of day is associated with circadian phenotype and PER3 genotype.